Battles over the Sexes - Kaebnick, Gregory E. (The Hastings Center report, 2012)
Several themes in this issue of the Hastings Center Report deserve mention. Entirely fortuitously, several shorter pieces in this issue discuss the nature of the doctor-patient relationship and the need for physicians to engage patients personally rather than only technically. Also, a special supplement to this issue addresses the shifting terrain of the debate about the use of animals in medical research. Perhaps the most prominent topic in the issue, however, is the physical modification of women's genitals. Both articles address this topic, and though there are significant differences between the two articles, both circle specifically around the question of whether the modification of women's genitals may be driven by cultural norms of womanhood and how women differ from men, and both comment not just on the questions but on the social debate about them.